Morphometric characteristics and the content of plastid pigments of the needles of Picea pungens depending on the distance from the highways - V. P. Bessonova; O. A. Ponomaryova (Biosystems Diversity, 2017)
This article examines the condition of the Picea pungens Engelm. plants at various distances from urban highways with high traffic intensity. The objects of the study were the trees P. pungens, whose age was about 35 years. The plants grow on four plots. The control plot is located in the conditionally clean zone; the plot 1 – 120 m from the road, plot 2 – at a distance of 10 m and plot 3 – on the median dividing strip of the road. It is established that in plants growing at a distance of 120 m from the highway and in the control plot, there was no difference in the parameters of the annual growth of shoots. In plants growing at a distance of 10 m from the road, a decrease in the length and mass of the shoot was determined. In the immediate vicinity of the highrway (on the median strip of the road), the growth rates of shoots decreased most significantly. A similar pattern was observed in the effect of distance from the road on the number of needles per unit length of shoot. The highest amount of chlorophyll a in the needles of spruce, regardless of the variant, was found in May, later it decreased in the summer months, and then increased slightly in September in all variants of the experiment. A similar pattern is also characteristic of changes in the chlorophyll content. The concentration of chlorophyll a in the needles of trees growing at a distance of 120 m from the highway, almost did not differ from plants in the clean zone. At a distance of 10 m its content was less, and for plants growing on the median strip of the highway, the amount of this form of green pigment decreased by 35% of the reference values. The content of chlorophyll b, like a, is not statistically different in the needles of the trees in the control plot and in plot 1. In plants of plots 2 and 3 its concentration decreased with respect to control. The sum of the green pigments a + b was the same in the needles of the control plot plants and those120 m from the road. In the experimental plots 2 and 3 the amount of chlorophyll a + b in the needles of the P. pungens was smaller than in the control and in plot 1. Depending on the sampling month, the difference with the control ranged from 14.7% to 21.0%. The content of carotenoids in the needles was spiny, low in plants at a distance of120 m from the road, and the highest in specimens that growing in the immediate vicinity of the road.